Membangun Strategi Pemasaran Pada Kedai Kopikaka - Saberina, Sabilla; Aprianti, Vika; Rusnendar, Elan (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2022)
Current business developments after Covid have started to creep back up, this is shown by the survival of the coffee business and the strengthening growth of the coffee business again. One of the innovations that is currently trending among the people of the city of Bandung is culinary delights in the form of cafes with aesthetic and instagrammable nuances that can attract visits and attention from consumers. Furthermore, consumer behavior in trade relations is influenced by the business culture that usually applies in that country. So understanding the business culture in a country will really help smooth business relationships both in building communication with trading partners. It is hoped that this can also develop potential not only seen in the product marketing aspect but also the importance of the role of strategy development in order to achieve profit optimization. For this reason, the development and increase in the competitiveness of coffee products targeted by the government has targeted a series of production and trade policies for coffee products. Therefore, it can be said that Indonesia has the potential to increase competitiveness by regularly marketing kaka coffee to various corners in order to build a marketing strategy that synergizes not only kaka shops in particular but the coffee sector in general.